Addressing urban informality since the design studio. Improving Public Space in Informal Settlements in Bogotá - Hernández García, Jaime; Sierra, Martha (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
The article presents and analyses the results of a research project and pedagogical action on the exploration of socio-spatial dynamics in informal settlements in Bogotá and the proposals of public space developed, in a summer international design studio with students from Colombia and México, in which members of the community also took part. The workshop sought to encourage students’ reflection on popular public space and to understand the difficulties and responsibilities when facing the informal city. In addition to the cultural exchange with students of different countries that facilitates a more complete and complex vision of the discipline. The article argues the importance of these tasks for the training of future architects and the contribution to the thinking and development of large areas of our Latin American cities.